Serine racemase is expressed in islets and contributes to the regulation of glucose homeostasis. Issue 6 (1st November 2016) - Lockridge, Amber D.; Baumann, Daniel C.; Akhaphong, Brian; Abrenica, Alleah; Miller, Robert F.; Alejandro, Emilyn U.
ABSTRACT: NMDA receptors (NMDARs) have recently been discovered as functional regulators of pancreatic β-cell insulin secretion. While these excitatory receptor channels have been extensively studied in the brain for their role in synaptic plasticity and development, little is known about how they work in β-cells. In neuronal cells, NMDAR activation requires the simultaneous binding of glutamate and a rate-limiting co-agonist, such as D-serine. D-serine levels and availability in most of the brain rely on endogenous synthesis by the enzyme serine racemase (Srr). Srr transcripts have been reported in human and mouse islets but it is not clear whether Srr is functionally expressed in β-cells or what its role in the pancreas might be. In this investigation, we reveal that Srr protein is highly expressed in primary human and mouse β-cells. Mice with whole body deletion of Srr (Srr KO) show improved glucose tolerance through enhanced insulin secretory capacity, possibly through Srr-mediated alterations in islet NMDAR expression and function. We observed elevated insulin sensitivity in some animals, suggesting Srr metabolic regulation in other peripheral organs as well. Srr expression in neonatal and embryonic islets, and adult deficits in Srr KO pancreas weight and islet insulin content, point toward a potential role for Srr in pancreatic development. These data reveal the first evidence that Srr may regulate glucose homeostasis in peripheral tissues and provide circumstantial evidence that D-serine may be an endogenous islet NMDAR co-agonist in β-cells.